THE IMPLEMENTATION OF GAMIFICATION CONCEPT INSIDE ONLINE CLASSROOM ACTIVITIES TO PROMOTE STUDENTS’ ENGAGEMENT - Jonathan, Feryan Christ; Recard, Michael (IJIET (International Journal of Indonesian Education and Teaching), 2021)
Online learning has made massive development nowadays. Due to the spread of Covid-19, the government made a policy to prohibit physical meetings in schools. However, this new policy caused a problem of engagement in online learning. During the lesson, students are giving slow and minimum responses to the teacher’s instruction. This happens in most of the school that operates online learning. Therefore, a solution to improve engagement in online classroom is needed. The implementation of the gamification concept is one of the great alternatives. The implementation of this concept has reaped positive results from various fields, including education. With the right application, this method can be a powerful tool to teach in online learning.